SC19 Let's make some TOAST – development of team obstetric and anaesthetic simulation training. (November 2018) - Ferns, Janis; Egbase, Elizabeth; Kandasamy, Gomathy; Hall-Jackson, Megan; Murray, Fiona
Abstract : Introduction: The effective functioning of the multidisciplinary team (MDT) in obstetrics has been targeted for improvement in multiple national reports. Recommendations include team training, skills and drills, and simulation of emergencies. 1 Despite these, the MDT is persistently cited as requiring improvement, impacting on patient safety. 1 Team training as sole focus has not been explored much in obstetrics. Responding to training needs with service development, we designed a course specifically focused on obstetric team dynamics and training in established MDTs. Methods: The Team Obstetric and Anaesthetic Simulation Training (TOAST) course was based on the TeamSTEPPS™ model of team work. 2 This prioritises training in established MDTs. The course aimed to integrate obstetric MDT members working together in our hospital. The first part of the one-day course was workshops on team training and dynamics, including a team game which provided examples of behaviours applicable to the obstetric MDT. The second part consisted of two simulation scenarios of evolving crises showcasing competing priorities for the MDT; this promoted deliberate practice of team work skills and behaviours. Debriefs focused on approaches to improve team working behaviour. Post-course feedback was sought immediately after. Results: The pilot course in July 2017 had 10 candidates from midwifery, obstetrics, anaesthetics and nursing. Another course in February 2018 had 8 candidates from midwifery, obstetrics and anaesthetics. Post-course feedback showed 90% from the first course and 100% from the second found it very or extremely useful and 100% would recommend it to colleagues. Understanding of other MDT members' roles improved or very much improved (points 4 and 5 on 5-point Likert scale) in 72% of candidates. Figure 1 shows how useful all candidates found specific sessions. Discussion and conclusion: We describe the development and implementation of a team training course for obstetric MDTs. This unique course focuses on team dynamics and training rather than practice drills of emergencies. Team training as well as simulation-based exercises have been recommended as patient safety strategies that healthcare organisations should adopt. 3 The TOAST course is an education development that encompasses both. Feedback supports the benefits of this team training, breaking down professional hierarchical barriers. Additional advantages include its low cost, replicability and trainability to other areas; similar training was developed for paediatrics in our hospital. Long-term effectiveness is an ongoing challenge recognised in the literature. 4 Inter-professional education surveys were employed in the last course, but longer-term monitoring and reinforcement is a future area for evaluation. References: MBBRACE-UK. Saving Lives, Improving Mothers' Care – Lessons learned to inform maternity care from the UK and Ireland Confidential Enquiries into Maternal Deaths and Morbidity 2013–15 December 2017. Available from https://www.npeu.ox.ac.uk/downloads/files/mbrrace-uk/reports/MBRRACE-UK%20Maternal%20Report%202017%20-%20Web.pdf [Accessed: 10 April 2018]. King HB, Battles J, Baker DP, et al. TeamSTEPPS™: Team strategies and tools to enhance performance and patient safety. In: Henriksen K, Battles JB, Keyes MA, Grady ML (eds.), Advances in Patient Safety: New Directions and Alternative Approaches (Vol. 3: Performance and Tools) 2008. Rockville, MD: Agency for Healthcare Research and Quality (US). Shekelle PG, Pronovost PJ, Wachter RM, et al. The top patient safety strategies that can be encouraged for adoption now. Ann Intern Med2013;158:365–8. Salas E, Rosen MA, King H. Managing teams managing crises: Principles of teamwork to improve patient safety in the Emergency Room and beyond. Theoretical Issues in Ergonomics Science 2007;8(5):381–94.